Peralihan Hak Atas Tanah Yang Menjadi Objek Sengketa Dalam Perspektif Penegakan Hukum: 1. Akibat Hukum Peralihan Hak Atas Tanah Yang Menjadi Objek Sengketa, 2. Prospektif Penegakan Hukum Terhadap Sengketa Peralihan Hak Atas Tanah - Adeka Andari Pernia Deka (Magister Kenotariatan, Universitas Jambi, 2021)
Dispute land cases in Indonesia in 2019 reached 30,817 cases, which was dominated by the typology of registration of conveyance of land rights. This shows that the reconstruction of the transfer of rights is not being perfectly understood by society, authority and others. The essence of this particular problem is in physical and juridical data on land rights which frequently shifts due to unqualified of deep land subject obligations in maintaining physical and juridical data its self. The purpose of this research is to figure out the legal consequences of rights conveyance to dispute lands and what are the prospects of law enforcement on future transfer of land rights disputes. The type of this research is juridical normative research which uses the statutory and conceptual approach method by using the theory of authority and law enforcement. The results show that the legal consequences of the transfer of rights over land that becomes the object of dispute, namely freehold and deed of transfer of land rights could be cancelled and declared null and void. This is because it is not fulfilled the subjective and objective requirements of the validity of an agreement and obligations land subject to safeguard physical data and juridical data which are an important part of a proof of ownership of land rights. Law enforcement perspective on the transfer of land rights disputes based on Government Regulation 24 of 1997 relies on the subject of land rights and deeds of stipulation of transfer of rights and other parties which are the basis for this transfer of rights to the land.